The Use of Channel-Purge Storage for Gastrointestinal Endoscopes Reduces Microbial Contamination. (3rd June 2015) - Saliou, Philippe; Cholet, Franck; Jézéquel, Julien; Robaszkiewicz, Michel; Le Bars, Hervé; Baron, Raoul
<x content-type="archive" xml:space="preserve">Abstract</x> Storage cabinets for heat-sensitive endoscopes (SCHEs) are designed to store gastrointestinal (GI) endoscopes in a clean, dry and well-ventilated cupboard to prevent microbiological proliferation. The use of SCHEs in a GI endoscopy unit has significally reduced the rate of contaminated endoscopes (13.0% vs 45.0%, P<.001). Infect. Control Hosp. Epidemiol. 2015;36(9):1100–1102